Analysis of the Supreme Court's Decision Regarding the Judicial Review of the Governor of Aceh Regulation Number 5/2018: The Siyasah Al-Qadhaiyyah Approach [Analisis Siyasah Al-Qadhaiyyah Terhadap Putusan Mahkamah Agung Nomor 39 P/Hum/2018 tentang Uji Materil Peraturan Gubernur Aceh Nomor 5/2018] - Syuhada Syuhada; Edi Yuhermansyah; Ulfa Yuranisa (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2021)
Abstract: This paper aims to examine the Supreme Court's (MA) Decision Number 39-P/HUM/2018 regarding the right to judicial review of the Aceh Governor's Regulation Number 5/2018 concerning the Jinayat Procedural Law. This decision relates to the petition for judicial review of the applicant regarding Article 30 of the Governor's Regulation which states that the caning is carried out in an open place at the Correctional Institution, or Detention Center, or Detention Center Branch. In essence, the Supreme Court does not accept applications from applicants. The problem is how the Supreme Court Judges consider the rejection of the request for review of the Aceh Governor Regulation, and how the siyasah al-qadha'iyah analysis of the Supreme Court judge's decision. The results of the analysis that the consideration of the Supreme Court Judge in the case of the Supreme Court's decision refers to the legal standing of the applicant. According to the Supreme Court, the petitioners have absolutely no legal standing because the provisions of Article 31 paragraph (2) of Law Number 3 of 2009 concerning the Supreme Court have not been fulfilled. The applicant is in an inappropriate position and has no legal standing. The applicant is unable to prove the loss of his rights to the enactment of the Pergub. The Supreme Court judge's decision is under the siyasa al-qadha'iyah review. The Supreme Court Justice has the right to reject, accept, or cancel regulations that have been made by the government through examining articles based on clear reasons and arguments. The Supreme Court has very clearly and unequivocally stated its considerations in rejecting the application. The refusal is following the rules of Islamic law, requiring that a decision must be accompanied by certain arguments (al-dalil). The decision of the supreme judge is also determined based on considerations of benefit. Abstrak: Tulisan ini hendak mengkaji Putusan Mahkamah Agung (MA) Nomor 39-P/HUM/2018 tentang hak uji materiil Peraturan Gubernur Aceh Nomor 5/2018 tentang Hukum Acara Jinayat. Putusan ini berhubungan dengan permohonan uji materiil pemohon menyangkut Pasal 30 Pergub yang menyatakan bahwa pencambukan dilakukan di tempat terbuka di Lembaga Pemasyarakatan, atau Rumah Tahanan, ataupun Cabang Rumah Tahanan. Intinya, MA tidak menerima permohonan dari pemohon. Permasalahan ialah bagaimana pertimbangan Hakim MA terkait penolakan permohonan pengujian Peraturan Gubernur Aceh tersebut, dan bagaimana analisis siyasah al-qada’iyah terhadap putusan hakim MA tersebut. Hasil analisis bahwa pertimbangan Hakim MA dalam perkara putusan MA mengacu pada legal standing pemohon. Menurut MA, para pemohon sama sekali tidak mempunyai legal standing karena ketentuan Pasal 31 ayat (2) UU Nomor 3 Tahun 2009 tentang MA tidak terpenuhi. Pemohon berada pada posisi yang tidak tepat dan tidak mempunyai legal standing. Pihak pemohon tidak mampu membuktikan kerugian haknya atas diberlakukannya Pergub tersebut. Putusan hakim MA sudah sesuai dengan tinjauan siyasah al-qadha’iyah. Hakim Agung memiliki hak untuk menolak, menerima, atau membatalkan peraturan yang telah dibuat oleh pemerintah melalui pengujian pasal-pasal dengan berdasarkan pada alasan dan dalil yang jelas. MA dalam telah sangat jelas dan tegas menyatakan pertimbangannya dalam menolak permohonan tersebut. Penolakan tersebut sesuai dengan kaidah-kaidah fikih, mengharuskan satu keputusan harus disertakan dengan dalil-dalil (al-dalil) tertentu. Putusan hakim agung juga ditetapkan berdasarkan pertimbangan kemaslahatan.